Knowledge of Hepatitis C risk factors is lower in high incidence regions(1) - Knick, Terry (J Community Health, 2019)
BACKGROUND: Despite ambitious goals to eliminate hepatitis C virus (HCV) in the United States by 2030, the majority of those infected are not aware of their diagnosis, and only a small minority have been cured. A lack of knowledge regarding risk factors and treatment may contribute to low cure rates. We aimed to evaluate HCV knowledge and the association of risk factor knowledge with HCV incidence. METHODS: In fall 2017, a survey regarding HCV knowledge was disseminated through social media, web link, and in person throughout the state of Virginia. RESULTS: The survey was completed by 613 individuals. Residents of high-incidence counties identified fewer risk factors (5.6 vs 6.1 of 9, p=0.04), a difference that remained significant when controlling for education and age (p=0.03). Fewer participants in the high-incidence group recognized snorting drugs to be a risk factor (25% vs 36%, p=0.01). Only 38% of all respondents correctly identified HCV to be curable. CONCLUSION: Knowledge of HCV risk factors is lower in high incidence regions. These results identify a critical knowledge gap in the general population at a time of ongoing HCV transmission. Public health interventions must target these gaps in high-incidence regions as part of comprehensive disease prevention programs.